Antibacterial and Antioxidant Properties of Macrocyclic Schiff Bases with Vanadium(V) Complexes - Pawar, Vatsala; Joshi, Sunil; Uma, V. (Asian Journal of Chemistry, 2012)
Macrocyclic Schiff bases have been synthesized by the condensation of acetyl acetone with semicarbazide hydrochloride and thiosemicarbazide in presence of methanol. Further, their oxovanadium complexes have been synthesized by using vanadium acetylacetone. The structural assignment of these compounds has been made on the basis of m.f., TLC, m.w. determination, conductivities, elemental analysis and UV, IR and 1H NMR spectral data. The synthesized compounds were screened for their in vitro growth inhibiting activity against different strains of bacteria viz., Staphylococcus aureus, Bacillus licheniformis, Escherichia coli and Micrococcus luteus (ATCC) and were compared with the standard antibiotic oflaxocin. Also in vitro antioxidant activity of all compounds was determined by nitric acid free radical scavanging assay.